PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING DI WAROENG SPESIAL SAMBAL YOGYAKARTA - Fereshti Nurdiana Dihan; Faisal Hidayat (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2020)
This research is related to how the effect of reward and performance on employee performance with work discipline as an intervening variable at outlets of Waroeng Special Sambal in Yogyakarta. The purpose of this research is to know the effect of reward to work discipline, the effect of punishment to work discipline, the effect of work discipline to employee performance, the effect of reward to employee performance, the effect of punishment to employee performance, the effect of reward to employee performance with work discipline as an intervening variable, and the effect of punishment to employee performance with work discipline as an intervening variable at outlets of Waroeng Special Sambal in Yogyakarta. Respondents of this research were 117 outlet employees of Waroeng Special Sambal Yogyakarta. The data collecting method used is using a questionnaire then analyzed by regression analysis and path analysis. The results of this research show that reward has a positive and significant effect on work discipline and employee performance, then punishment also has a positive and significant effect to work discipline and employee performance. Besides, there is the indirect effect of reward on employee performance through work discipline, and also the indirect effect of punishment on employee performance through work discipline.